Spatiotemporal Variations in Abundance and Biomass of Planktonic Ciliates Related to Environmental Variables in a Temporal Pond, Argentina - Küppers, Gabriela Cristina (2012)
This report describes the structure and seasonal dynamics of ciliated protozoa associated with variations in physicochemical characteristics of the environment in a temporary pond in Buenos Aires Province, Argentina. Plankton samples were obtained, and physicochemical variables were measured monthly for 2 yr. In total, 50 planktonic ciliates were recorded. The highest species richness occurred during the pond’s filling and stable-hydric phases. Upon the pond’s desiccation, the number of ciliate species decreased, with the lowest values being recorded in spring; while the highest abundance and biomass values were observed before drought periods. Ciliate diversity tended to be higher after a drought but decreased with pond desiccation. Most ciliate species were rare and found during filling periods. Vorticella convallaria, Pelagostrobilidium wilberti, and Coleps hirtus were dominant; Cyclidium glaucoma, Strobilidium caudatum, Pseudochilodonopsis piscatoris, Limnostrombidium viride, L. pelagicum, and Chilodonella sp. were common; and Pelagostrombidium mirabile and Rhabdostyla sp., an epibiont on cladocerans, were occasional. The 1st axis and the sum of all axes in the canonical correspondence analysis explained a significant portion of the variance in the ciliate data. Autumn and winter samples were grouped together corresponding to the highest conductivities, high precipitation, and low temperatures, properties which characterized the filling and stable-hydric periods. Species were mainly distributed according to conductivity and temperature gradients along the 1st canonical axis. The structure and temporal dynamics of planktonic ciliates from this temporary pond varied with changes in the physicochemical characteristics of the environment which were determined by flooding and desiccation.